2019
DOI: 10.1002/jcp.28599
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial effects of radiofrequency hyperthermia and radiotherapy in the presence of magneto‐plasmonic nanoparticles on MCF‐7 breast cancer cells

Abstract: Here, the effects of combinatorial cancer therapy including radiotherapy (RT) and radiofrequency (RF) hyperthermia in the presence of gold-coated iron oxide nanoparticles (Au@IONPs), as a thermo-radio-sensitizer, are reported. The level of cell death and the ratio of Bax/Bcl2 genes, involved in the pathway of apoptosis, were measured to evaluate the synergistic effect of Au@IONPs-mediated RF hyperthermia and RT. MCF-7 human breast adenocarcinoma cells were treated with different concentrations of Au@IONPs. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
0
22
0
1
Order By: Relevance
“…6 , both BAX and BCL2 were strongly activated in cancer cells due to the thermal stimulus, while they were not in normal cells. Furthermore, the ratio of BAX / BCL2 , which is an index of apoptosis promotion, also differed dramatically between cancer and normal cells after thermal stimulation 15 .
Figure 6 Relative mRNA expression levels of apoptosis-related genes.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 , both BAX and BCL2 were strongly activated in cancer cells due to the thermal stimulus, while they were not in normal cells. Furthermore, the ratio of BAX / BCL2 , which is an index of apoptosis promotion, also differed dramatically between cancer and normal cells after thermal stimulation 15 .
Figure 6 Relative mRNA expression levels of apoptosis-related genes.
…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that HSP, which confers thermotolerance to cells, can also be expressed by mechanical stimulation rather than heat shock 25 . Alternatively, it was recently reported that combinations of hyperthermia and other stimuli enhanced the cell killing effect 10 , 15 , 26 , 27 . On the other hand, in previous studies, owing to the lack of a system that achieves immediate temperature regulation, there was a gap between the set temperature and the actual realized culture temperature to which cells were exposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since HT-induced cytotoxicity and DNA damage can be observed during 24 h and these effects can be recovered by time as reported in the literature [41,42], it is essential to evaluate the cell metabolic activity with same time scale. In contrast, clonogenic assay, which is typically used in radiation research, measures the reproductive cell death by assessing the long-term effect after 2-3 weeks [43].…”
Section: Discussionmentioning
confidence: 99%
“…The previous study demonstrated that mild hypothermia or fever-range hyperthermia had inhibitory effect on viability/proliferation in glioblastoma, prostate, lung, breast cancer cell lines [16]. However, the other study has found that hyperthermia alone had no signi cant effect on breast cancer cells but its combination with radiotherapy has been useful for apoptosis [17]. Here, there is the gap in our knowledge and why we are doing this study on hyperthermia effects.…”
Section: Introductionmentioning
confidence: 99%